Interface study of SiCp/6061Al composite - Adebisi, Adetayo A.; Maleque, Md. Abdul; Bello, Kamilu Adeyemi (Elsevier Inc., 2020)
Interface characteristics and reaction mechanism play a major role in determining the properties of Al-SiCp composite. Therefore, the aim of this study is to investigate the interface mechanism of Al-SiCp composite developed by stir casting process. The SiCp is preheated for 2 hrs at 1200 °C prior to addition into the Al alloy melt. Moreover, 1 wt% Mg is added to enhance the wettability properties of the Al and SiCp. It was observed that the surface morphology of oxidized SiCp shows the presence of SiO2 (silicon dioxide) layer. This layer prevents SiCp from being attacked by 6061 Al alloy. The reaction mechanism of Al and Mg with SiO2 on the surface of oxidized SiCp resulted to the formation of MgO (magnesium oxide) and MgAl2O4 (magnesium aluminate) which act as diffusion barrier between Al and SiCp at the interface. This reaction products suppresses the potential formation of unwanted and undesired Al3C4 (alumina carbide) which degrades the properties of the Al-SiCp composite.